2015
DOI: 10.1111/jfs.12223
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stress Factors on the Growth of Spoilage Yeasts Isolated From Apple‐Related Environments in Apple Juice

Abstract: This study aimed to evaluate the effects of temperature, pH, sugar content and antimicrobial components on the growth of 11 yeast isolates in apple juice (12°B rix, pH 4.0). The results showed that reduction of the storage temperature to 4C could achieve a complete inhibition of test strains, and the temperature required to kill all the initial yeast inoculum (10 3 cfu/mL) within 20 min ranged from 46 to 55C, depending on the isolate. However, high sugar content enabled test strains to survive in what would ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Regarding biochemical tests, results shown in Table 2 indicate that all the species are osmo-tolerant and grow well in 50 and 60% glucose broth. Zygosaccharomyces rouxii was the most osmoresistant yeast, which is consistent with an earlier study that had reported that the species can support sugar content as high as 70°Brix (approximately 875 g/l glucose) and is able to grow at water activities as low as 0.60 (Wang et al 2016;Marvig et al 2015). It is admitted that this feature of osmotolerance is linked to the production of compatible solutes (i.e., polyols) such as D-arabitol according to many authors (Sharma and Sharma 2017;Evrendilek 2012).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding biochemical tests, results shown in Table 2 indicate that all the species are osmo-tolerant and grow well in 50 and 60% glucose broth. Zygosaccharomyces rouxii was the most osmoresistant yeast, which is consistent with an earlier study that had reported that the species can support sugar content as high as 70°Brix (approximately 875 g/l glucose) and is able to grow at water activities as low as 0.60 (Wang et al 2016;Marvig et al 2015). It is admitted that this feature of osmotolerance is linked to the production of compatible solutes (i.e., polyols) such as D-arabitol according to many authors (Sharma and Sharma 2017;Evrendilek 2012).…”
Section: Resultssupporting
confidence: 91%
“…The viability feature is a key element for biotechnological process involving recycling or re-circulation. In this respect, Wang et al (2016) reported that non-Saccharomyces species found in fermented food could be isolated only from the early stages of fermentation. Therefore, the studied strains isolated from Btana are promising candidates in fermentation process as they can sustain under extended periods of fermentation and high ethanol stress.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that all Z. rouxii strains tested are susceptible to THY and T-CNM, and THY has a better antifungal activity against Z. rouxii. In comparison with other antifungal agents, THY showed better fungistatic and fungicidal activities against Z. rouxii than ferulic acid (MIC of 1.17 mg/ml), p-coumaric acid (MIC of 1.23 mg/ml), cinnamic acid (MIC of 0.35 mg/ml), vanillin (MIC more than 2.28 mg/ml), citral (MIC of 0.17 mg/ml and MFC of 0.34 mg/ml), limonene (MIC of 0.66 mg/ml and MFC of 2.64 mg/ml), carvacrol (MIC of 0.128 mg/ml), eugenol (MIC of 0.43 mg/ml and MFC of 0.86 mg/ml), and potassium metabisulfite (MIC more than 0.256 mg/ml) (Cai et al, 2019;Chavan & Tupe, 2014;Wang et al, 2016b). In another report, THY exhibited better inhibitory activity against the growth of Z. rouxii in apple juice (30 • Brix) than T-CNM, carvacrol, hydroxycinnamic acids, and synthetic preservatives (potassium sorbate and sodium benzoate) (Wang & Sun, 2020).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…can occasionally be isolated from low-pH juices [55,56]. On the opposite, R. mucilaginosa and S. cerevisiae are commonly involved in the spoilage of fruit products [48,51,57,58]. M. caribbica is mostly known as an endophyte yeast, but has been isolated from spoiled minimally-processed pineapple [26,59].…”
Section: Identification Of Fungal Isolates Involved In Spoilage Of Minimally-processed Pineapplementioning
confidence: 99%